Satisfaction Of Outpatient Services For National Health Insurance Patients In Universitas Muhammadiyah Malang Public Hospital - Laila, Aulia Maghfirotul; Setiawan, Eko Rahman (Jurnal Pendidikan Kesehatan, 2021)
The level of patient satisfaction on service is an important factor for developing service provider system that responsive to patient complaints, minimize costs and time, and maximize patient services. Patient satisfaction can be seen based on the dimensions of reliability, assurance, tangibles, empathy, and responsiveness. This study is intended to identify patient satisfaction with outpatient services based on five dimensions of satisfaction at the General Hospital of the University of Muhammadiyah Malang in 2019. Descriptive quantitative used as research design in this study. The research instrument is a questionnaire, and the data were taken from purposive sampling technique with 100 respondents. This study found that Satisfaction based on several dimensions of reliability is, satisfied 96 percent dissatisfied 4 percent, guarantee is satisfied 92 percent dissatisfied 8 percent, tangibles satisfied 89 percent dissatisfied 11 percent, empathy satisfied 90 percent 10 percent dissatisfied, and responsiveness is satisfied 97 percent dissatisfied 3 percent patients. The highest satisfaction rating is on the reliability indicator, the reliability of officers in providing services. Although the assessment of patient satisfaction has shown that the patient was quite satisfied, the results obtained did not indicate a value of 100 percent. This research can be input to maintain and improve services, so that outpatients are satisfied with the service.